Motivation of Students in Learning English for Nurse Anesthesiology at ITEKES Bali - Dewi, Kadek Maya Cyntia; Suryati, Ni Wayan Novi; Rusanti, Putu; Wismadewi, I Gusti Agung Galuh; Susanta, I Putu Agus Endra (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
In the globalized healthcare system, nurse anesthesiologists require strong English communication skills to ensure safe and effective patient care (Hidayat, 2020). This study investigates the motivational factors influencing students enrolled in the Advanced English for Nurse Anesthesiology course at ITEKES Bali. Using a mixed-method design, data were collected from 30 students through questionnaires and semi-structured interviews. The findings reveal that both intrinsic factors (personal growth, confidence, and professional readiness) and extrinsic factors (career advancement, institutional expectations, and international opportunities) significantly influence students' motivation. Task-based learning, role-plays, and clinical simulations emerged as highly motivating instructional strategies. The study highlights the importance of aligning course design with students’ motivational drivers to optimize learning outcomes. The findings suggest that educators should emphasize practical, interactive activities that foster confidence while reducing language anxiety.